34. Optimization in HDR gynecological brachytherapy. (December 2017) - Vande Woestyne, M.; Madelis, G.; Potet, H.; Servagi, S.; Gaillot, N.
Abstract : Introduction: The distal vagina HDR brachytherapy is the final treatment of cervical cancer, as a complementary treatment to surgery and/or external radiation therapy. The goal of this study was to evaluate the coverage of the Clinical Target Volume and the maximum dose received by the Organs at Risk, related to the rectal volume and the optimization method. Methods: This is a retrospective study causing 2 groups of 5 patients each, treated by HDR brachytherapy. A group with both bladder and rectal volumes <100 cc and a group with a bladder volume <100 cc and rectal volume >100 cc. The CTV-T, rectal, sigmoidal and bladder volumes have been delineated in Oncentra BrachyPlanning TPS. The prescribed total dose was 6 Gy in 5 mm from the applicator surface over a length of 5 cm with source position intervals of 5 mm. The treatment planning has been performed without treatment optimization, with a manual standard optimization (MO) consisting of a 20% increase of the source dwell times in the 1st centimeter (the proximal to the vaginal scar), and a target point optimization (TP), consisting in optimizing the dose in the CTV-T dose points. The CTV-T coverage criteria and the dose received by 2 cc of the OAR have been compared using the Wilcoxon test. Results: The two optimization techniques have increased the coverage of the CTV-T receiving the prescribed dose by 7.15% (MO) and 6.15% (TP) for the group 1 and by 11.14% (MO) and 5.23% (TP) for the group 2. Although non-significant, the coverage of the CTV-T is always less satisfactory with the TP optimization. The D2 of the rectum has increased by 4.84% (MO) and 6.19% (TP) for the 1st group and by 6.09% (MO) and 5.20% (TP) for the 2nd group. The D2 of the sigmoid has increased by 11.14% (MO) and 6.02% (TP) for the 1st group and by 11.61% (MO) and 5.06% (TP) for the 2nd group. The D2 of the bladder has increased by 7.92% (MO) and 6.04% (TP) for the 1st group and by 8.67% (MO) and 5.29% (TP) for the 2nd group. There has been no significant difference in the D2 of the OAR between the two optimization techniques. Conclusion: The manual ant target point optimization have significantly improved the CTV-T coverage (albeit a significant but acceptable increase of the OAR maximum dose). No significant difference has been observed between the two optimization techniques.